Construction of Geological Knowledge-based Systems of Railway Route Selection - Lv Xikui; Zhou Xiaoping; He Bin (Institute of Advanced Engineering and Science, 2014)
According to the diversity of geological conditions involved in railway location design, different types of geological objects were classified and indexed, and proposed the modeling method based on multiple sub-bases. It used the computer's internal and external representation in geological knowledge representation. In computer external, it used object-oriented class-rules knowledge representation model, added credibility to the object-oriented knowledge representation model, and then achieved fuzzy representation of knowledge. In order to achieve visual representation of external knowledge representation, text, images and three-dimensional virtual reality technology were used. According to the ambiguity of geological knowledge, it realized uncertainty reasoning of the part based on rule condition and conclusions.